2008
DOI: 10.1017/s1751731107001048
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adult ewes during early and mid-pregnancy. 1. Effects of plane of nutrition on ewe reproduction and offspring performance to weaning

Abstract: The objective of this study was to determine the effects of plane of nutrition during early and mid-pregnancy on the performance of mature ewes and their offspring. From day 0 to day 39 post mating (early pregnancy, EP), 82 multiparous ewes were fed to provide either 60% (low, L), 100% (medium, M) or 200% (high, H) of predicted metabolisable energy (ME) requirements for maintenance, following a synchronised mating. From day 40 to day 90 (mid-pregnancy, MP), ewes were provided with either 80% (M) or 140% (H) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
2
40
1
1
Order By: Relevance
“…Previous studies (McCrabb et al, 1992) have shown that feeding ewes that were in good condition at the beginning of the study (day 30), above maintenance requirement, reduced placental size, which is positively correlated with lamb birth weight. However, Muñ oz et al (2008) showed that increasing feed level in mid-pregnancy from 0.8 to 1.4 maintenance did not influence birth weight. The lack of an Deferred (extended) grazing and silage for pregnant ewes effect of offering silage indoors (even at higher levels of feeding) on lamb birth weight is probably associated with diet type and feeding method.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies (McCrabb et al, 1992) have shown that feeding ewes that were in good condition at the beginning of the study (day 30), above maintenance requirement, reduced placental size, which is positively correlated with lamb birth weight. However, Muñ oz et al (2008) showed that increasing feed level in mid-pregnancy from 0.8 to 1.4 maintenance did not influence birth weight. The lack of an Deferred (extended) grazing and silage for pregnant ewes effect of offering silage indoors (even at higher levels of feeding) on lamb birth weight is probably associated with diet type and feeding method.…”
Section: Discussionmentioning
confidence: 87%
“…The effects of plane of nutrition in early and mid-pregnancy are reported in an accompanying paper (Muñ oz et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The ewes were randomly allocated to treatments and subsequently balanced for LW, BCS, ewe breed and sire breed. The ewes were naturally mated once following a synchronisation regime as described by Muñ oz et al (2008). Treatments were applied from day 214 to day 90 post mating and consisted of control; receiving no supplement; and Se supplement receiving 1 g of Selplex R (Alltech, Belfast, NI, UK), an organic source of Se, providing an intake of 0.5 mg Se per ewe per day.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations